2005
DOI: 10.1017/s0033291705005726
|View full text |Cite
|
Sign up to set email alerts
|

Immigrants from the former Soviet Union, 5 years post-immigration to Israel: adaptation and risk factors for psychological distress

Abstract: Psychological readjustment apparently takes longer than other processes of adaptation. Several years after immigration, social and psychological factors have a more important role for the well-being of immigrants than their material conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 25 publications
(34 reference statements)
2
47
0
1
Order By: Relevance
“…Despite these positive anticipations, the respondents experienced upcoming migration as a relatively stressful event. However, their average stress level decreased after migration, and there was no difference between T 1 and T 2 assessments of psychological well-being, even though a decrease in well-being is typical for the postmigration stage (e.g., Kirkcaldy et al, 2005;Lerner et al, 2005;Ritsner & Ponizovsky, 1999;Ward, 2001). These positive findings may be explained by the different role of affective dimension as compared to the other two acculturation dimensions: Decreased psychological stress may be seen as a reactive response to ethnic migrants' positive acculturation experiences in the behavioral dimension of acculturation after migration (cf., Jasinskaja-Lahti, 2008).…”
Section: Discussionmentioning
confidence: 91%
“…Despite these positive anticipations, the respondents experienced upcoming migration as a relatively stressful event. However, their average stress level decreased after migration, and there was no difference between T 1 and T 2 assessments of psychological well-being, even though a decrease in well-being is typical for the postmigration stage (e.g., Kirkcaldy et al, 2005;Lerner et al, 2005;Ritsner & Ponizovsky, 1999;Ward, 2001). These positive findings may be explained by the different role of affective dimension as compared to the other two acculturation dimensions: Decreased psychological stress may be seen as a reactive response to ethnic migrants' positive acculturation experiences in the behavioral dimension of acculturation after migration (cf., Jasinskaja-Lahti, 2008).…”
Section: Discussionmentioning
confidence: 91%
“…Several factors affecting psychological distress in the general population also operate on the psychological distress of immigrants and refugees. In general, immigrant women report a higher mean level of distress than immigrant men (Gonzalez-Castro and Ubillos 2011, Lerner, Kertes, andZilber 2005, Levecque, Lodewyckx, andBracke 2009) although this www.intechopen.com difference may not be statistically significant in older immigrants (Chou 2007, Ritsner, Ponizovsky, andGinath 1999). Similarly, financial hardship (Gonzalez-Castro and Ubillos 2011, Lerner, Kertes, andZilber 2005, Sundquist et al 2000), poor self-reported health (Chou 2007, Lerner, Kertes, andZilber 2005) and recent stressful events (Lerner, Kertes, andZilber 2005, Thapa andHauff 2005) act as risk factors whereas family cohesion (Lerner, Kertes, andZilber 2005, Yip, Gee, andTakeuchi 2008) and the sense of control over one's life (Lerner, Kertes, andZilber 2005, Sundquist et al 2000) play a protective role.…”
Section: In Immigrantsmentioning
confidence: 99%
“…The influence of other long-established risk and protective factors is more uncertain. Most studies have found no statistically significant effect of age (Levecque, Lodewyckx, and Bracke 2009, Thapa and Hauff 2005, Yip, Gee, and Takeuchi 2008 on the psychological distress of immigrants whereas the evidence is mixed for unemployment (Lerner, Kertes, and Zilber 2005, Levecque, Lodewyckx, and Bracke 2009, Thapa and Hauff 2005, education (Chou 2007, Levecque, Lodewyckx, and Bracke 2009, Sundquist et al 2000 and marital status (Chou 2007, Lerner, Kertes, and Zilber 2005, Thapa and Hauff 2005. Deciphering the relationships between psychological distress and factors typical of immigrants is a difficult task because of the complex interplay of the context of migration, the ethno-cultural background of immigrants and the socio-cultural characteristics of the host country.…”
Section: In Immigrantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since time since immigration is one of the key indicators of acculturation [36,37], it is not surprising that both generations are similar and do not differ from veteran Israeli population with regard to mental morbidity and service use rates, The higher emotional distress found among immigrant parents [35] may partly explain their attribution of more behavioral problems to their children than parents of Israeli-born peers and significantly less prosocial behavior. However, parental distress or depression was not measured in our study and therefore this explanation is advanced as a hypothesis for future research.…”
Section: Services Usementioning
confidence: 99%